Performance enhancing substances in exercise settings: a systematic review - Tavares, Ana Sofia (2018)
Performance enhancing substances (PES) is used by gym/fitness users. This situation implies a public health problem since it has been shown that drugs such as Steroids, Stimulants, Erythropoietin, and Human Growth Hormone has significant performance-enhancing effects, which can lead to dangerous side effects or even fatal with long-term use. This systematic review aimed to analyze studies that describe attitudes, beliefs and knowledge, as conceptualized in Theory of Planned Behavior (TPB) influenced by the use of PES by gym/fitness center users and provide a framework on the state of the art in this theme, and thus allow the design and foundation of future research lines. Twenty-six articles were identified from a systematic approach following the PRISMA Statement via electronic databases and hand-searching bibliographies of reference lists. Only peer-reviewed primary research published in English, Portuguese and Spanish (1997-2016), focusing on gym/fitness center users regardless of age and gender and provide some information on psychosocial factors towards using PES were included in this review. Emergent themes conceptualized with the TBP concluded that the main reasons pointed for young male bodybuilders using steroids as a prevalent drug, regards aesthetic issues, improve muscle size, strength and performance. Important influences come from groups and instructors. Drugs are obtained from a variety of sources. Predisposition related to steroid use increase with years of physical training. Although some steroid users indicated a general lack of knowledge of the potentially harmful effects of drugs, others had high knowledge about drug's side effects. The TPB illustrated a relationship between psychosocial factors influencing gym users to use PES. TPB could be used in future research to provide a template when developing prevention programs to reduce the use of PES and promote new lines of investigation on this study groups, as well as different PES than steroids.